Violent conditions: The injustices of being. (July 2018) - Laurie, Emma W.; Shaw, Ian G.R.
Abstract: Violent conditions burn in the background of daily life. Consider the slow wounds of ecological violence, the crumbling cityscapes of austerity, or the mental trauma inflicted by capitalism. In this paper, we provide an account for understanding violence in and through conditions, drawing on the work of Johan Galtung and Gilles Deleuze in particular. Violent conditions are not the property of individuals or monolithic structures: they are the existential climates by which localized subjects and worlds condense into being. In making this argument, we not only advance scholarship on the geographies of violence, but also make a sustained case for how and why condition is an important social, political, and ontological heuristic. Our examination is framed by unearthing the complex conditions and discontents of capitalism. Violent conditions forcefully constrain, traumatize, and poison the very resources of our becoming. Accordingly, we provide a map for exploring the geographies of violent conditions across four interrelated sections. (1) The Virtual, (2) Truncated Life, (3) Time, (4) Common Sense . Collectively, these explain how violence is embedded in the flesh and bones of our worlds. The paper finishes by discussing the injustices of being and the possibilities for peace.